2020
DOI: 10.1186/s12864-020-6703-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in children with juvenile idiopathic arthritis: characteristics, biomarker identification, and usefulness in clinical prediction

Abstract: Background: Recent studies have suggested that the gut microbiota is altered in children with juvenile idiopathic arthritis (JIA). However, age, sex, and body mass index (BMI) were not matched in the previous studies, and the results are inconsistent. We conducted an age-, sex-, and BMI-matched cross-sectional study to characterize the gut microbiota in children with JIA, and evaluate its potential in clinical prediction. Methods: A total of 40 patients with JIA and 42 healthy controls, ranging from 1 to 16 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 71 publications
0
29
0
8
Order By: Relevance
“…In microbiome research, machine learning is used for taxonomic classification, beta-diversity analysis, binning, and compositional analysis of particular features. Commonly used machine learning methods include random forest (Vangay et al, 2019 ; Qian et al, 2020 ), Adaboost (Wilck et al, 2017 ), and deep learning (Galkin et al, 2018 ) to classify groups by selecting biomarkers or regression analysis to show experimental condition-dependent changes in biomarker abundance (Table 2 ).…”
Section: Statistical Analysis and Visualizationmentioning
confidence: 99%
“…In microbiome research, machine learning is used for taxonomic classification, beta-diversity analysis, binning, and compositional analysis of particular features. Commonly used machine learning methods include random forest (Vangay et al, 2019 ; Qian et al, 2020 ), Adaboost (Wilck et al, 2017 ), and deep learning (Galkin et al, 2018 ) to classify groups by selecting biomarkers or regression analysis to show experimental condition-dependent changes in biomarker abundance (Table 2 ).…”
Section: Statistical Analysis and Visualizationmentioning
confidence: 99%
“…In this regard, although promising, the results seem less consistent than in other areas as of few studies with a limited sample size have been carried out only on fecal samples. In particular, in a cohort of 39 patients with juvenile idiopathic arthritis, a random forest algorithm was used to discriminate patients from healthy controls (AUC 0.80) by integrating information of 12 genera including Anaerostipes , Dialister , Lachnospira , and Roseburia from fecal samples [ 102 ]. Size and quality of datasets are of utmost importance in ML.…”
Section: Future Direction: Artificial Intelligence (Ai) and Its Application In The Prediction Of The Link Between Oral Microbiome And Rhementioning
confidence: 99%
“…12 This has been further substantiated in a paper by Qian et al in which they found that four genera of short-chain fatty acid (SCFA) producing microbes were useful as a clinical predictor of JIA. 2 As SCFAs have important immunomodulatory functions including differentiation of anti-inflammatory regulatory T cells, IL-10 production, and proinflammatory TH17 suppression, the growing evidence continues to find the deregulatory actions of the immune system as the guilty culprit. This is supported by studies that show that alterations in Tcell populations may promote inflammation and modulation of these populations may be targets for treatment.…”
Section: Pathogenesismentioning
confidence: 99%
“…1 JIA has an estimated prevalence of 1 in 1000 making it one of the most common rheumatological conditions affecting children leading to complications such as joint damage and vision loss. 1,2 This childhood condition is inflammatory in nature leading to extraarticular manifestations, permanent joint damage, and significant morbidity with persistence into adulthood. 1 The International league of associations of rheumatology (ILAR) developed a classification system in the mid 1990's, the most recent update in 2001, subdividing JIA ABSTRACT Juvenile idiopathic arthritis is the most common inflammatory rheumatological condition affecting children.…”
Section: Introductionmentioning
confidence: 99%